Formulations of the deformable foundation contact problems - Kalanta, Stanislovas; Grigusevičius, Andrius; Krutinis, Antanas (Journal of Civil Engineering and Management, 2002)
Up to now in many works a construction on elastic foundation was modelled by the Winkler's hypothesis. In this paper the flexible plate-foundation system is investigated as an interaction of separate elastic bodies, which lie on the contact surface. Such a problem formulation allowed to make more exact the stress and strain distribution in the construction and the contact surface, to estimate the dead weight of the foundation. The presented numerical examples are realised using computer programme COSMOS/M. The obtained results show evidently the expediency of the new method application in practice.First Published Online: 30 Jul 2012